Estudio de derecho comparado en materia de contratación pública entre Ecuador, Dinamarca, Finlandia Y Suiza en temas de exclusión de personas basado en La Directiva 2014/24/UE - Mogrovejo Castillo, Humberto Felix (2023)
The present Curricular Integration Work is titled: "Study of comparative law in public procurement between Ecuador, Denmark, Finland, and Switzerland on the exclusion of individuals based on Directive 2014/24/EU. "My personal goal to investigate and analyze this issue is to evidence the impact on the Ecuadorian State. The research specifically focuses on Administrative Law and its branch of Public Procurement; this area is critical as it deals with the management and issues that increase when handling the State's financial resources in procedures related to the acquisition or leasing of goods, execution of public works, or provision of services, including consulting services. The lack of control in analyzing the profile of each contractor participating in the awarding of different public procurement processes becomes evident. Contrary what is happening in Denmark and Finland, which, based on Directive 2014/24/EU of the European Parliament and Council, obliges all contracting authorities to exclude any economic operator related to or involved in a) Participation in a Criminal Organization, b) Corruption, and c) Money Laundering, Switzerland's regulations are also influenced by adding notions of the 3 subparagraphs of Article 57 of the directive to improve transparency and position themselves as countries with less corruption globally in the field of public procurement. In the present Curricular Integration Work, materials and methods were used, including surveys of legal professionals, whose results were used to propose guidelines aimed at ensuring the proper use of public resources and improving transparency in public procurement in Ecuador.